Pemberdayaan Peternak Sapi Pola Paronisasi melalui Pembuatan Pupuk Bokashi di Desa Oeletsala, Kabupaten Kupang - Melkianus Dedimus Same Randu; Ferdinan Suharjono Suek; I Gusti Komang Oka Wirawan; Agustinus Semang (Institut Pertanian Bogor, 2020)
Oeletsala Village is an area in Kupang Regency that dominates the community who runs a business of feedlot (paronization) of Bali cattle. Paronization activities were implemented hereditary, but less explored the utilization of livestock waste (feces) causing environmental pollution and supporting the population of flies as a mechanical vector of thelaziasis. This community service aims to improve the knowledge and skills of farmer group partner members related to making bokashi fertilizer. Community service activities are conducted in the Nij Baki Group, which has 24 members. Implementation of activities methods include extension, plot demonstration, assistance, and evaluation. The results of activities achieved were the production of 300 kg Bokashi fertilizer and the revenue from the sale of Bokashi fertilizer amounted to IDR 375.000. Community service activities have provided positive benefits in the form of increased knowledge about the benefits of Bokashi fertilizer (87.50%) and skills for making bokashi fertilizer (79.17%).